Wheat spike fertility: inheritance and relationship with spike yield components in early generations. Issue 3 (8th April 2015) - Martino, Diana L.; Abbate, Pablo E.; Cendoya, María G.; Gutheim, Florencia; Mirabella, Nadia E.; Pontaroli, Ana C.; Saranga, Y.
Abstract In wheat, grain number is considered as the product of spike dry weight (SDW) and the number of grains per unit of SDW, that is an indicator of spike fertility (SF). The aim of this study was to determine the heritability of SF and the effect of early selection for high SF on its relationship with other spike yield components. Two field experiments were conducted in the south‐eastern Pampas (Argentina) with 400 F2 and F2:3 families obtained from two crosses between varieties with contrasting SF (PIG/SSN and B10/KCJ). Heritability estimates in PIG/SSN and B10/KCJ were, respectively, 0.60 and 0.51 by variance component analysis, 0.43 and 0.43 by F2 : F3 parent–offspring regression and 0.30 and 0.28 by realized heritability analysis. The existence of transgressive segregation (i.e. the occurrence of families with SF values that were more extreme than those of the parents) was observed. The top 25% F3 families with the highest SF had 12% more grains per spike, despite a 13% and 5% decrease in SDW per spike and weight per grain, respectively, than the remaining families. These results give support to the application of early selection for high SF.